2011
DOI: 10.1007/s13213-011-0230-9
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of soil contaminated with copper using Rhamnolipids produced from Pseudomonas aeruginosa MTCC 2297 using waste frying rice bran oil

Abstract: Rhamnolipids production by Pseudomonas aeruginosa MTCC 2297 was studied, using waste frying rice bran oil as carbon substrate. Response surface methodology was employed to arrive at the optimum production condition. Maximum rhamnolipids production (7.6 g/l) was attained with waste frying rice bran oil at 34.8 g/l, with sodium nitrate at 3.9 g/l. Optimum temperature and initial pH were found to be 34°C and 7.4. Batch washing experiments were used to evaluate the efficiency of rhamnolipids on remediating copperc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…These amphiphilic molecules have the capacity to form complexes with trace metals at the soil interface and to desorb trace metals from soil matrix, further increasing their solubility and bioavailability in the soil solution (Venkatesh and Vedaraman, 2012).…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
“…These amphiphilic molecules have the capacity to form complexes with trace metals at the soil interface and to desorb trace metals from soil matrix, further increasing their solubility and bioavailability in the soil solution (Venkatesh and Vedaraman, 2012).…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
“…Juwarkar, Dubey, Nair, and Singh () observed that when di‐rhamnolipid produced by Pseudomonas aeruginosa BS2 was applied in the remediation of metal contaminated soil, the removal efficiency of metals shows the order of Cd = Cr>Pb = Cu>Ni. Venkatesh and Vedaraman () investigated the remediation of soil contaminated by copper using rhamnolipids produced by Pseudomonas aeruginosa MTCC 2297 with a batch washing experiment, and observed that 2% of rhamnolipids removed 74% and 71% of copper from soil with initial concentrations of 4,484 and 474 ppm, respectively.…”
Section: Remediation Of Metal Contaminationmentioning
confidence: 99%
“…Juwarkar, Dubey, Nair, and Singh (2008) observed that when di-rhamnolipid produced by Pseudomonas aeruginosa BS2 was applied in the remediation of metal contaminated soil, the removal efficiency of metals shows the order of Cd = Cr>Pb = Cu>Ni. Venkatesh and Vedaraman (2012) (Dahrazma et al, 2008;Zhong, Yang, et al, 2015), which in turn influence metal removal. For example, Aşçı et al (2007) The addition of other chemicals to rhamnolipid solutions may enhance the metal removal efficiency.…”
Section: Remediation Of Metal Contaminationmentioning
confidence: 99%
“…The efficiency of Cu removal with RAM can be high when soil is not co-contaminated with other HMs. Venkatesh and Vedaraman applied a 2% RAM solution to soil spiked with only Cu and were able to remove 74% of the HM, even though its initial concentration was nearly 5000 mg/kg (Venkatesh and Vedaraman 2012).…”
Section: The Effect Of Single Soil Washing With Biosurfactants On Hm mentioning
confidence: 99%
“…In environmental remediation, they can act as ligands and have a strong affinity for HMs due to their carboxyl groups. Up to now, most studies on the use of RAM have involved Cu, Cd, Ni, Pb or Zn removal from soils via soil washing (at varying pH, concentrations of RAM or washing times) or soil flushing (at different concentration of RAM, flushing time or flow rate) (Mulligan and Wang 2006;Juwarkar et al 2007;Venkatesh and Vedaraman 2012;Wan et al 2015).…”
Section: Introductionmentioning
confidence: 99%